Psychological profile and unexpected pain in oral lichen planus: A case–control multicenter SIPMO studya. (2nd March 2021) - Adamo, Daniela; Calabria, Elena; Coppola, Noemi; Lo Muzio, Lorenzo; Giuliani, Michele; Bizzoca, Maria Eleonora; Azzi, Lorenzo; Croveri, Fabio; Colella, Giuseppe; Boschetti, Ciro Emiliano; Montebugnoli, Lucio; Gissi, Davide; et al.
Abstract: Objectives: To analyze psychological profiles, pain, and oral symptoms in patients with oral lichen planus (OLP). Materials and methods: 300 patients with keratotic OLP (K‐OLP; reticular, papular, plaque‐like subtypes), 300 patients with predominant non‐keratotic OLP (nK‐OLP; erythematosus atrophic, erosive, ulcerative, bullous subtypes), and 300 controls were recruited in 15 universities. The number of oral sites involved and oral symptoms were recorded. The Numeric Rating Scale (NRS), Total Pain Rating Index (T‐PRI), Hamilton Rating Scales for Depression and for Anxiety (HAM‐D and HAM‐A), Pittsburgh Sleep Quality Index (PSQI), and Epworth Sleepiness Scale (ESS) were administered. Results: The OLP patients, especially the nK‐OLP, showed higher scores in the NRS, T‐PRI, HAM‐D, HAM‐A and PSQI compared with the controls ( p ‐value < .001 ** ). A positive correlation between the NRS, T‐PRI, HAM‐A, HAM‐D, and PSQI was found with the number of oral symptoms and number of oral sites involved. Pain was reported in 67.3% of nK‐OLP and 49.7% of K‐OLP cases with poor correspondence between the site of lesions and the site of the symptoms. Conclusions: Mood disorders are frequently associated with OLP with an unexpected symptomatology correlated with the number of oral symptoms and with the extension of disease suggesting a peripheral neuropathy.